1997
DOI: 10.1007/s003810050061
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous intracranial hemorrhage of structural origin during the first year of life

Abstract: Symptomatic intracranial hemorrhage (ICH) in term infants is not common, but when it occurs it is usually secondary to trauma, coagulation disorders and/or hypoxia. The possibility of a structural cause for an infantile ICH is unfortunately not seriously considered until very late. In this paper we report the cases of five full-term infants, each of whom developed ICH secondary to a structural lesion during the 1st year of life. Three presented during the newborn period. A congenital saccular aneurysm of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 83 publications
0
53
1
Order By: Relevance
“…Generally, infantile aneurysms are more often found in the MCA (around 40%) or in the posterior circulation (20–30%) [51,52,53,54]. The most common presenting symptom of aneurysm in infants is intracerebral hemorrhage, with incidences between 60 and 78% reported [51,55,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, infantile aneurysms are more often found in the MCA (around 40%) or in the posterior circulation (20–30%) [51,52,53,54]. The most common presenting symptom of aneurysm in infants is intracerebral hemorrhage, with incidences between 60 and 78% reported [51,55,56,57].…”
Section: Discussionmentioning
confidence: 99%
“…Although the precise pathophysiological mechanisms of hemorrhage into brain tumors are still under investigation, primitive tumors carry higher risk of bleeding than other types. 21) The cause might be found in the dysmorphic configuration of the tumor vessels with endothelial abnormalities such as alteration of tight junctions, which render these lesions more hemorrhage-prone. 15) In this case, histological examination revealed the most likely criteria for peripheral PNET, based on the absence of staining against neuroepithelial antigens, and positive staining for CD99 in the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Lasjaunias et al demonstrated the tendency for the rate of dissecting aneurysm to increase as patient age decreases, and in their study, dissecting aneurysms were seen in eight of 11 patients less than two years old 1 . Other studies have suggested the possibility that some neonatal spontaneous dissecting aneurysms are caused by traumatic stress during the birth process 8,19,24 . These aneurysms often occur around the tentorial incisura, and this may be one reason most dissecting aneurysms are seen in the posterior circulation in very young children 25 .…”
Section: Case Reportmentioning
confidence: 99%
“…Less than 2% of all childhood aneurysms occur during infancy 8 , and the incidence of ruptured aneurysms in infants is extremely low. The location and morphology as well as the clinical and radiological features of pediatric cases differ from those of adult cases 1,9 .…”
Section: Introductionmentioning
confidence: 99%